Disease Diagnostics: Lipidic Cubic Phases as a Versatile Platform for the Rapid Detection of Biomarkers, Viruses, Bacteria, and Parasites (Adv. Funct. Mater. 2/2016). (January 2016) - Vallooran, Jijo J.; Handschin, Stephan; Pillai, Samyuktha M.; Vetter, Beatrice N.; Rusch, Sebastian; Beck, Hans‐Peter; Mezzenga, Raffaele
Abstract : With worldwide epidemic outbreaks occurring on a regular basis, there is urgent need to improve and establish new strategies toward rapid, simple, and affordable detection of target analytes. Birefringence generated from versatile lipid based liquid crystal cubic phase leads to a unique optical signal that can be used to detect analytes of medical interest, including bacteria, viruses, and parasites, as shown by R. Mezzenga and co‐workers on page 181.